Characteristics and 3,5-dichlorocatechol 1,2 -dioxygenase gene location of Pseudomonas sp GT241-1 - ZHONG Wen-hui; HE Guo-qing; ZHENG Ping; SUN Ming; YU Zi-niu (浙江大学学报. 农业与生命科学版, 2001)
A 2,4-dichlorophenol degrading bacterium strain, designated as GT241-1, was isolated from the soil around drainage area of several factories which produced 2,4-dichlorophenol. It was identified as Pseudomonas sp. Strain GT241-1 can decompose 91% of 2, 4-dichlorophenol with original concentration of 90 mg/L within 48 hours. GC/MS analysis revealed that the strain can degrade 2,4-dichlorophenol completely, without accumulation of intermediate metabolite. Heat treatment at 38℃ made 1.9% of GT241-1 strains lose its 2,4-dichlorophenol degrading ability. Strain GT241-1 has two big plasmids. Southern blot results showed that the 3, 5-dichlorocatechol 1,2-dioxygenase gene of strain GT241-1 locates on its about 11kb EcoRI/XbaI fragment.